Фортификация Сугдеи второй половины Х-ХI вв. - Майко, В.В. (Археологический альманах, 2012)
In the article the features of fortification of Sugdeja are considered in a Middle Byzantine period. In that medieval town fortress walls are studied on five independent areas general length more than 70 m. Most information was got on an area so-called Quarter 1 and on the area of curtain XV. The analysis of curtain testifies to the capital re-erecting of primary fortification however with the use of basic part of curtain for defense of city. Walls on these areas are complemented laying on lime solution and use of elements of laying «in a fir-tree». The opened gate testify about major repairs. In two cases a primary gate was stopped up, and in place of them the new are organized. Next to a gate battle towers were built. Analogical receptions demonstrate excavations of Chersonese. As well as in Sugdeja, the most late tracks of repair of fortification buildings are dated of XI—XII centuries. Thus, fortification receptions, fixed in the provincial- Byzantine cities of Taurica, are distinguished by negligence and building haste, eliminating beauty and monumental of fortress buildings. Violating the norms of Byzantine fortification, to the walls dwellings and economic apartments were built on. This circumstance was explained, above all things, with strengthening of danger from the side of nomads.